Historical development of adjective accentuation in Croatian (suffixless, *-ьnъ and *-ъkъ adjectives) - Kapović, Mate (Baltistica, 2011)
The article deals with the historical development of the accentuation of suffixless (root), *-ьnъ and *-ъkъ adjectives. Their development is analyzed in detail from their Proto-Slavic origin to their modern reflexes in Štokavian, Čakavian and Kajkavian dialects. The dialectal data is taken from previously published dialectal descriptions, but also from the author's own extensive and previously unpublished field data – mostly from Posavina and Vrgorska krajina. The analysis of the historical development of adjectival accentuation can provide us with interesting insights that go beyond the scope of adjectives. A careful historical study of adjectival accentuation reveals many interesting early changes and isoglosses in Štok/Čak/Kajk, helps us understand the modern dialectal forms, which are then far more useful from a comparative Slavic perspective and shed light on some important prosodic changes that occurred in the history of Štok/Čak/Kajk.  KROATŲ KALBOS BŪDVARDŽIŲ KIRČIAVIMO RAIDA (NEPRIESAGINIAI BŪDVARDŽIAI IR BŪDVARDŽIAI SU PRIESAGOMIS *-ьnъ, *-ъkъ)SantraukaStraipsnyje pristatoma kroatų kalbos būdvardžių kirčiavimo raidos apžvalga. Atskirai aptariama nepriesaginių būdvardžių ir būdvardžių su priesagomis *-ьnъ, *-ъkъ kirčiavimo raida nuo slavų prokalbės formų iki refleksų šiuolaikinėse štokavų, čakavų bei kaikavų tarmėse. Remiamasi anksčiau paskelbtais šnektų aprašais, taip pat paties autoriaus surinkta gausia iki šiol neskelbta tarmių medžiaga – daugiausia iš Posavinos ir Vrgorska Krajinos. Kruopšti būdvardžių kirčiavimo tarmėse analizė leidžia geriau suprasti ne ne tik pačių būdvardžių kirčiavimo istoriją, bet ir gerokai platesnes lyginamosios slavų kalbotyros problemas: straipsnyje atskleista nemažai reikšmingų ankstyvajame raidos etape vykusių prozodinių pakitimų ir štokavų-čakavų-kaikavų izoglosų, naujai interpretuotos kai kurios dabartinės tarmių formos.Indexation
Keywords: IWoBA; Balto-Slavic accentology; historical accentology; accentuation; dialectology; Croatian; adjective; accentuatian; suffixless; *-ьnъ; *-ъkъ